Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.cattod.2019.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Understanding effects of Ni particle size on steam methane reforming activity by combined experimental and theoretical analysis

Abstract: Fundamental understanding of the size dependent activity is essential to harness powers of the nanocatalysts.Here we report an experimental and theoretical study of the Ni particle size effect on activity of steam methane reforming (SMR) to achieve a better understanding of the size dependence of kinetic behavior at an atomic level. A kinetic study illustrated the higher forward methane turnover frequency on the smaller sized Ni particles. The size dependent activity was well reproduced by microkinetic modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…Another important factor to consider is that the CDM reaction has been proven to be structurally sensitive to nickel particle size; small nickel particles showed high methane cracking activity [69]. That can be explained by the lower activation barriers of CH x species dissociation on uncoordinated crystallographic planes (e.g., Ni (553) or Ni (100)) compared with the packed surface (e.g., Ni (111)), which are greater on small-sized particles [70]. On the contrary, a large amount of Ni (111) surfaces are present on the large nickel particles.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor to consider is that the CDM reaction has been proven to be structurally sensitive to nickel particle size; small nickel particles showed high methane cracking activity [69]. That can be explained by the lower activation barriers of CH x species dissociation on uncoordinated crystallographic planes (e.g., Ni (553) or Ni (100)) compared with the packed surface (e.g., Ni (111)), which are greater on small-sized particles [70]. On the contrary, a large amount of Ni (111) surfaces are present on the large nickel particles.…”
Section: Discussionmentioning
confidence: 99%
“…CMD reaction is also structurally sensitive to Ni particle size where small Ni particles show high methane decomposition activity 146 . This can be explained by the lower activation barriers of methyl species dissociation on uncoordinated crystallographic planes such as Ni (553) or Ni (100) compared with the packed surface Ni (111), which are greater on small‐sized particles 146,147 . Different from small Ni particles, a large amount of Ni (111) surfaces exists on the large Ni particles.…”
Section: Ni‐based Catalystmentioning
confidence: 99%
“…Besides above, Ni catalysts were also widely used in methane reforming reactions, which is a main process for hydrogen production in current chemical insustry. [ 205‐209 ] It has been demonstrated that the catalytic performance tightly relies on Ni particle size. For example, Chen and co‐workers reported that small Ni particles exhibited a higher activity than large ones in the size range of 2 to 16 nm in steam methane reforming (SMR) over Ni catalyst.…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%
“…For example, Chen and co‐workers reported that small Ni particles exhibited a higher activity than large ones in the size range of 2 to 16 nm in steam methane reforming (SMR) over Ni catalyst. [ 206 ] By combining experimental and theoretical analysis, they claimed that Ni(211) is the most active surface, compared with Ni(111) and Ni(100). Thus, the size‐dependent activity was attributed to the decrease of the fraction of Ni LCSs as Ni particle size increases, consistent with the work by Nørskov et al .…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%